2018
DOI: 10.1039/c8sc00481a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic perspective and functional activity of insulin in amylin aggregation

Abstract: This work provides the first-ever complete atomic model of insulin–amylin aggregates, identifying the specific interactions that stabilize the insulin–amylin complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“… 24 , 26 Furthermore, we previously investigated this recognition motif between insulin and amylin fibril-like oligomers. 27 Herein, we applied the recognition motif of the insulin with the homology sequence of the amyloids, similarly as proposed by the previous experimental studies. 24 , 26 It was proposed that insulin chain B binds to the central hydrophobic core (CHC) domain of Aβ that contains the diphenylalanine motif.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 , 26 Furthermore, we previously investigated this recognition motif between insulin and amylin fibril-like oligomers. 27 Herein, we applied the recognition motif of the insulin with the homology sequence of the amyloids, similarly as proposed by the previous experimental studies. 24 , 26 It was proposed that insulin chain B binds to the central hydrophobic core (CHC) domain of Aβ that contains the diphenylalanine motif.…”
Section: Resultsmentioning
confidence: 99%
“…To interact insulin chain B with Aβ, we have taken into account the recognition motif in two orientations between insulin and Aβ 1–42 fibril-like oligomers across the fibril ( Figures 2 a and 2 b), similarly as we previously examined for the insulin-amylin fibril-like oligomer recognition motif. 27 While the CHC domains in the “U-shape” fibril-like oligomers are exposed and allow the insulin to bind the insulin, in the “S-shape” fibril-like oligomer the CHC domains are buried inside the hydrophobic core of the fibril and thus do not allow for interactions with insulin ( Figure S4 ). The initial interactions of insulin with model A in two orientations exhibited models A1 and A2 ( Figure S5 ), and the interactions with model B are illustrated in models B1 and B2 ( Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…37 A number of molecular dynamics (MD) simulations discovered that the binding of insulin with Ab and hIAPP aggregates affected the pathological aggregation of Ab and hIAPP. 38,39 MD simulations also revealed that Ab and hIAPP can cross-seed each other to form enlongated fibrils and laterally associated fibrils, which in turn exacerbate the neurodegenerative process. [40][41][42] To address this issue, we reported a drug repurposing study of aromadendrin ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Availability of injectable insulin formulation has been a breakthrough in diabetes management in achieving long-term glycemic control and preventing complications ( Baram et al., 2018 ; Heller et al, 2007 ; Moroder and Musiol, 2017 ; Owens et al., 2001 ; Xiong et al., 2019 ; Zaykov et al., 2016 ); it still, however, suffers from certain disadvantages including temperature-sensitive fibrillation in solution and development of subcutaneous tumor-like mass designated as “amyloidoma” at the site of injection ( Hua and Weiss, 2004 ; Ivanova et al., 2009 ; Nilsson, 2016 ; Woods et al., 2012 ; Yumlu et al, 2009 ). Worldwide efforts were thus made to develop thermostable insulin either by making recombinant insulin species with mutations or stabilizing native insulin with salts, Zn 2+ ions, and small molecules such as meta-cresol ( Frankær et al., 2017 ; Gong et al., 2014 ; Han et al., 2017 ; Kachooei et al, 2014 ; Lee et al, 2014 ; Patel et al, 2018 ; Saithong et al, 2018 ; Wang et al, 2011 ; Zheng and Lazo, 2018 ).…”
Section: Introductionmentioning
confidence: 99%